1945
DOI: 10.6028/jres.035.013
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in the physical adsorption of nitrogen on bone char and other adsorbents

Abstract: An investigation has been made of some characteristics of hysteresis in the pbysical adsorption of nitrogen on bone char, activated carbon, silica gel, and coconut-shell charcoal at 77.4 0 K. It was found that hysteresis became less pronounced in the order given, occurring only slightly in coconut-shell charcoal and only from high relative pressures in the pressure range in which the Langmuir equation was not obeyed. It was shown that it was highly probable that a true steady state was attained in the pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1948
1948
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…All PNDCs show similar shaped curves, with a similar contribution of hysteresis. A hysteresis loop refers to the space in each isotherm where the adsorption and desorption curves do not overlap . From IUPAC standards of sorption isotherms, all PNDCs display a type 4 isotherm.…”
Section: Data Analysis/resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All PNDCs show similar shaped curves, with a similar contribution of hysteresis. A hysteresis loop refers to the space in each isotherm where the adsorption and desorption curves do not overlap . From IUPAC standards of sorption isotherms, all PNDCs display a type 4 isotherm.…”
Section: Data Analysis/resultsmentioning
confidence: 99%
“…A hysteresis loop refers to the space in each isotherm where the adsorption and desorption curves do not overlap. [49] From IUPAC standards of sorption isotherms, all PNDCs display a type 4 isotherm. These isotherms are characterized by a distinct hysteresis loop that is indicative of mesopores on the carbon-based surface.…”
Section: Brunauer-emmet-teller Analysismentioning
confidence: 99%
“…As time-dependent results presented in this article are expressed in terms of dimensionless time, it is useful to have an order of magnitude for t r . According to an article by Gleysteen and Deitz 22 published in 1945 on the sorption of nitrogen on carbon adsorbents, steady state is attained in about 20 min, meaning that sorption does not (1984), in Ruthven's book on adsorption, 23,24 sorption experiments of ethane on Linde 4A zeolite are cited, showing about the same time to steady state. Somewhat more extensive measurements were reported in 2010 by Battistutta et al 8 on the sorption of methane, nitrogen, and carbon dioxide on dry coal.…”
Section: Background Materialsmentioning
confidence: 99%
“…The evidence for interpreting the isotherms as an indication of water being held on the charcoal by capillary condensation is also strong: (1) No satisfactory explanation of hysteresis in desorption has so far been advanced for any process other than capillary condensation. A recent paper by Gleysteen and Deitz (72) suggested that if one applies the multilayer theory of Brunauer, Emmett, and Teller to the adsorption isotherms at high relative pressures in place of the capillary condensation theory and then assumes that desorption involves a larger heat than adsorption, hysteresis can be accounted for. It remains to be explained why the heat of desorption should be larger than the heat of adsorption.…”
Section: B Rate Of Adsorption Of Watermentioning
confidence: 99%